2012
DOI: 10.1111/ijlh.12014
|View full text |Cite
|
Sign up to set email alerts
|

Stability of athlete passport parameters during extended storage

Abstract: Key blood results can be relied upon for at least 7 days if storage temperature is kept at 4-6 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 11 publications
4
29
0
1
Order By: Relevance
“…Improved stability was observed in samples stored as K2-EDTA-anticogulated blood sample at refrigeration [5,9,10,[17][18][19]. Significant time and temperature related morphological alterations could happen with the long extended storage of blood on refrigeration (Figure 1) [17,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved stability was observed in samples stored as K2-EDTA-anticogulated blood sample at refrigeration [5,9,10,[17][18][19]. Significant time and temperature related morphological alterations could happen with the long extended storage of blood on refrigeration (Figure 1) [17,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies, which were conducted using refrigerated temperature show that WBC, RBC, and HGB parameters, were constant up to 72 h [21,22]. Only Ashenden et al recently confirmed that haemoglobin was stable for at least 168 h using the Sysmex XT-2000i instrument, when maintained temperature between 4°C and 6°C [18]. Where our study finds that these parameters like WBC counts, RBC counts and HGB level were statistically stable up to 126 h, 186 h and 90 h respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown previously that the 36‐h window appears overly conservative. In our hands, key haematological variables were stable for at least 7 days provided that storage temperature was kept at 4–6 °C .…”
Section: Introductionmentioning
confidence: 89%
“…The stability of cellular components in EDTA for automated counting is limited: Hb concentration and RBC have been shown to be stable for up to 72 hours, automated total and differential white blood count for 24 hours (or longer, depending on analyser type) and platelet count stable for the same period ( 18 , 19 ). Swelling of red cells in EDTA will result in an increase in the MCV and haematocrit within 12 hours of collection.…”
Section: The Use Of Edta Anticoagulated Blood As Eqa Assay Materialsmentioning
confidence: 99%